ALIH FUNGSI LAHAN PERTANIAN MENJADI LAHAN PERUMAHAN DI KABUPATEN JEMBER - Yunita Reykasari; Lutfian Ubaidillah; Nikita Maulidya; Miftahul Huda (FAIRNESS AND JUSTICE, 2021)
The transfer of land functions which is quite ambiguous is faced by the government in relation to regulating policies on agricultural areas, especially in Jember district. Regional government obliged to accelerate the pace of economic growth through development housing and industrial development along with increasing population growth,while the government also needs to pay attention to efforts to  maintain as well maintain the existence of agricultural lands to meet the needs of the community incidentally is productive land. Without any effort to overcome the dilemma through improvement of regulations and policies issued previously, namely Regional Regulations Number 1 Year 2015 which is highly irrelevant to current conditions, the rate of decline agricultural land in Jember which has decreased since 2005-2013 will be increasingly high. In 2005 the area was 74,884.13 Ha decreased to 74,229.26 Ha in in 2013, where the area decreased by 654.87 hectares. This fact is also clouded with the rise of housing permits that are adjacent to water sources that hamper their use for irrigation purposes. In fact, the land crisis was caused by developers namely, land that is close to a water source is purchased by the developer so that the impact is not productive land around due to the impact of lack of water flow so that the soil with Such conditions can be considered a crisis land. Such conditions can categorized as an act of wetsonduiking (legal smuggling).